Masculinity and mental health treatment initiation for former political prisoners in Yangon, Myanmar - a qualitative investigation - Daniel P. Lakin; Kyaw Soe Win; Htin Aung; Khin Nyein Chan Soe; Bo Kyi; Arik V. Marcell; Wietse A. Tol; Judith K. Bass (BMC, 2021)
Abstract Background Men living in low- and middle-income countries are unlikely to seek mental health care, where poor healthcare infrastructure, differences in illness conceptualization, and stigma can impact treatment seeking. Vulnerable groups, such as former political prisoners, are more likely than others to experience potentially traumatic events that may lead to negative mental health outcomes. To improve the likelihood of successful engagement of vulnerable men in psychotherapy, it is necessary to identify factors that influence treatment adherence, and to better understand men's attitudes surrounding decisions to seek and initiate care. The purpose of this investigation was to explore themes of masculinity, treatment seeking, and differences between male former political prisoners who accepted and declined therapy in an urban low-income context. Methods We conducted a qualitative, interview-based investigation with 30 former political prisoners in Yangon, Myanmar who were eligible to receive mental health counseling provided by the non-governmental organization (NGO), Assistance Association for Political Prisoners. Men were initially screened using a composite questionnaire with items related to depression, anxiety, and posttraumatic stress symptom severity. After screening, if potential clients were identified as having probable mental health problems, they were asked if they would like to participate in a multi-session cognitive behavioral therapy program. Semi-structured, open-ended interviews were conducted with 15 participants who accepted and 15 participants who declined therapy. Interviews were transcribed and translated by local partners and thematically coded by the authors. We used thematic analysis to identify and explore differences in treatment-seeking attitudes between men who accepted and men who declined the intervention. Results Men described that being a community leader, self-reliance, morality, and honesty were defining characteristics of masculinity. A focus on self-correction often led to declining psychotherapy. A general lack of familiarity with psychological therapy and how it differed from locally available treatments (e.g. astrologists) was connected to stigma regarding mental health treatment. Conclusions Masculinity was described in similar terms by both groups of participants. The interpretation of masculine qualities within the context of help-seeking (e.g. self-reliance as refusing help from others versus listening to others and applying that guidance) was a driving factor behind men's decision to enter psychotherapy.